Tuberous Sclerosis Complex With Multiple Organ Tumors: Case Report and Literature Review - Zhang, Xinhe; Zhong, Xinping; Lin, Xuyong; Li, Xuedan; Tian, Haoyu; Chang, Bing; Wang, Ying; Tong, Jing; Wang, Ningning; Li, Dan; Jin, Xiuli; Huang, Die; et al. (Frontiers in Oncology, 2022)
We reported a rare case with involvement of multiple organs and space-occupying lesions. Initially, the patient was thought to be metastasis of pancreatic endocrine tumor. However, the patient was diagnosed as pancreatic neuroendocrine tumors, liver perivascular epithelioid tumors, splenic hamartoma, and renal angiomyolipoma by pathological examination after surgery. We performed genetic mutation detection to identify that tuberous sclerosis complex 2 gene (TSC2) presented with a heterozygous variant. Finally, the patient was diagnosed with possible tuberous sclerosis complex with multiple organ involvement. In addition, we reviewed the current molecular mechanisms and treatments for tuberous sclerosis complex. We also analyzed the relationship between TSC gene mutations and related tumors.